Residency Restrictions for Sex Offenders: Public Opinion on Appropriate Distances. (April 2015) - Anderson, Amy L.; Sample, Lisa L.; Cain, Calli M.
Although many states have enacted statewide residency restriction laws, others have left the need for, and content of, these laws to local municipalities. To better understand within-state variation in residency restriction laws, this study investigates the public's desire for these laws and the distances they feel restrictions should be from public spaces populated by children. We review both quantitative and qualitative data from a statewide survey to determine where the public feels sex offenders can live without threatening children. Our results are interpreted using the "dikes" perspective of public opinion to predict the passage and content of future of residency restriction laws.